Overruling Louisiana: Horizontal Stare Decisis and the Concept of Precedent - Legarre, Santiago (2021)
The article discusses two U.S. Supreme Court cases, Ramos v. Louisiana and June Medical v. Russo, which deal with the concept of stare decisis that approached horizontal precedent and overruling.